Super water-repellent coating composition
The water-based super water-repellent coating composition, featuring hydrophobic fine particles and a specific solvent blend, addresses the durability issues of conventional water-based coatings by maintaining superior water-repellent properties and film durability.
Patent Information
- Application Number
- JP2024021412
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-06
- Filing Date
- 2024-02-15
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-02-15
AI Technical Summary
Conventional water-based coatings with hydrophobic silica fine particles suffer from decreased water-repellent properties over time, leading to reduced durability of the coating film.
A water-based super water-repellent coating composition is developed, containing hydrophobic fine particle powder with a carbon content of 1.5% by mass or more, a mixed solvent made of water and an organic solvent with a specific Hansen solubility parameter, and a resin, while being substantially free of water-soluble polymers.
The composition achieves improved durability and sustained super water-repellent properties of the coating film, outperforming conventional compositions in terms of dispersibility, water repellency, and long-term performance.
Smart Images

Figure 2025037778000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous coating composition that exhibits super water repellency. [Background technology]
[0002] Traditionally, in the field of paint technology, solvent-based paints using organic solvents as solvents have been widely used, but in recent years, there has been a shift to water-based paints in which resins are dispersed in water in order to reduce health hazards to painters and air pollution. However, water-based paints have lower hardness than oil-based paints and are more susceptible to dirt such as dust, dirt, and other particles in the air. In addition, since the resin in water-based paints also contains hydrophilic parts, a significant amount of hydrophilic parts remain in the paint film even after drying. As a result, rainwater easily adheres to the paint film, causing problems such as rain streaks that impair the scenery, and deterioration of the paint film that causes peeling and swelling, which damages buildings and raises concerns about repairs such as replacement.
[0003] In recent years, therefore, there has been progress in the development of aqueous coating compositions that exhibit super water repellency, i.e., super water repellent coating compositions, and Patent Document 1 discloses a super water repellent coating composition that contains at least one type of hydrophobic silica microparticle powder, a dispersant, and a solvent. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 7129255 Summary of the Invention [Problem to be solved by the invention]
[0005] In Patent Document 1, a dispersant, i.e., a water-soluble polymer, is used to disperse hydrophobic silica fine particle powder in a water-based solvent in order to disperse the hydrophobic silica fine particle powder in the paint. However, when the present inventors carried out various tests on the superwater-repellent paint composition of Patent Document 1, they found that the water repellency of the coating film decreased over time, posing a problem in the durability of the coating film.
[0006] The present invention has been made in view of the above, and has an object to provide an aqueous, ultra-water-repellent coating composition containing hydrophobic fine particle powder, which is capable of forming a coating film with ultra-water repellency and has improved durability compared to conventional coating films. [Means for solving the problem]
[0007] The present inventors have conducted extensive research into the causes of the above problems with the superwater-repellent coating composition of Patent Document 1, and have found that the cause is that the superwater-repellent coating composition of Patent Document 1 contains a water-soluble polymer. In other words, because water-soluble polymers have good affinity with water, this affects the durability of the coating film.
[0008] Based on the technical idea of dispersing hydrophobic fine particle powder in a paint without substantially using a water-soluble polymer, the inventors have intensively investigated technical means for achieving this, and have completed the present invention.
[0009] That is, according to one aspect of the present invention, there is provided the following ultrawater-repellent coating composition. A super water-repellent coating composition for forming a super water-repellent coating film on a substrate, comprising: A composition comprising at least one hydrophobic fine particle powder (A), a mixed solvent (D) of water (B) and an organic solvent (C), and a resin (E), and is substantially free of a water-soluble polymer; the hydrophobic fine particle powder (A) has a carbon content of 1.5% by mass or more and a content thereof in the superwater-repellent coating composition of more than 0% by mass and 10% by mass or less; The Hansen solubility parameter of the mixed solvent (D) is 51.2MPa, which is the sum of the polarity term and the hydrogen bond term. 0.5 More than 57.7MPa 0.5The super water-repellent coating composition is as follows: Effect of the Invention
[0010] According to the present invention, it is possible to provide an aqueous ultra-water-repellent coating composition containing a hydrophobic fine particle powder, which is capable of forming a coating film with ultra-water repellency and has improved durability compared to conventional coating films. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The super water-repellent coating composition according to the present invention comprises at least one type of hydrophobic fine particle powder (A), a mixed solvent (D) of water (B) and an organic solvent (C), and a resin (E), and is substantially free of a water-soluble polymer. The following describes in detail the embodiments of the composition, but the present invention is not limited thereto.
[0012] <Hydrophobic fine particle powder (A)> The hydrophobic fine particle powder is a powder that is a substance with a small surface free energy and forms a fine uneven structure, and examples of such powder include hydrophobic oxide fine particle powder, composite oxide fine particle powder, and organic fine particle powder. In order to obtain a fine particle powder with a particle size on the order of nm, hydrophobic oxide fine particle powders such as silica, alumina, and titania are preferred, and one or more of these may be used. In particular, hydrophobic silica fine particle powder formed by subjecting the surface of silica fine particle powder to hydrophobic treatment is most suitable.
[0013] The M value has been known as a parameter indicating hydrophobicity. The M value is the concentration expressed in vol.% of methanol at which the treated powder begins to wet in a mixed solution of water and methanol. Generally, the higher the M value, the higher the hydrophobicity, and it is frequently used as a parameter when dispersing hydrophobic fine particle powder. However, the inventors' experiments have revealed that the parameter that has a greater effect on the hydrophobicity of the fine particle powder and the super-hydrophobicity of the paint is the carbon content rather than the M value, and the carbon content is used as a parameter indicating the hydrophobicity of the hydrophobic fine particle powder. That is, the hydrophobic group with low surface free energy is given to the outermost surface of the hydrophobic fine particle powder, but there is no limit to the type or number of the hydrophobic group, and the carbon content is 1.5 mass% or more, and more preferably 2.0 mass% or more. The carbon content can be analyzed by any conventional method. For example, it can be measured by quantifying the amount of carbon dioxide generated when the powder is oxidized in air or oxygen at a temperature of about 1000 to 1500 °C.
[0014] As described above, the hydrophobic fine particle powder (A) may be a hydrophobic oxide fine particle powder, a composite oxide fine particle powder, or an organic fine particle powder. Each of these will be described in detail below.
[0015] [Hydrophobic oxide fine particle powder] The hydrophobic oxide fine particle powder is a fine particle powder whose surface is modified with a hydrophobic functional group, and examples of the fine particle powder include silicon oxide, titanium oxide, aluminum oxide, zirconium oxide, cerium oxide, magnesium oxide, and zinc oxide. The method for hydrophobizing the surface of the oxide microparticle powder is not particularly limited as long as it is a method that incorporates fluorine or an alkyl group into the surface of the oxide microparticle powder, and examples of the method include methods using one or more organometallic compounds such as silylating agents, silane coupling agents, and alkylaluminums. The hydrophobic oxide fine particle powder is preferably a hydrophobic silica fine particle powder, and synthetic silica or natural silica is used. Synthetic silica is synthesized by a dry method such as a combustion method or an arc method, a precipitation method, or a wet method such as a gel method.
[0016] [Oxide composite fine particle powder] The oxide composite microparticle powder is a powder including a core oxide microparticle powder and a coating layer formed on the surface thereof. The core oxide microparticle powder is an aggregate structure (aggregate porous structure) in which a plurality of oxide microparticles (primary particles) are three-dimensionally connected, and examples of the oxide microparticle powder include the oxide microparticle powder described above. Meanwhile, the coating layer is formed inside and on the outer shell of the aggregate structure. There is no particular limitation on the method for preparing such an oxide composite microparticle powder, and for example, a polyfluoroalkyl methacrylate resin may be used as a coating material for the oxide microparticle powder, and a coating layer may be formed according to a known coating method, granulation method, or the like. More specifically, the oxide composite microparticle powder can be suitably prepared by a method including a step (coating step) of coating the oxide microparticle powder with a coating liquid in which a liquid polyfluoroalkyl methacrylate resin is dissolved or dispersed in a solvent.
[0017] [Organic fine particle powder] Examples of organic fine particle powders include organic fine particle powders of polytetrafluoroethylene (PTFE), polystyrene (PS), polymethyl methacrylate (PMMA), polyethylene (PE), polypropylene (PP), polycarbonate (PC), polyethylene terephthalate (PET), polyimide (PI), polyvinyl chloride (PVC), cellulose, etc., and these may be used alone or in the form of a mixture of two or more kinds.
[0018] Although the hydrophobic microparticle powder (A) has been exemplified above, the hydrophobic microparticle powder (A) is not limited to the exemplified ones, and in short, it is sufficient that the carbon content is 1.5 mass% or more. The upper limit of the carbon content is not particularly limited, but the upper limit of the industrially available one is, for example, 8.5 mass%.
[0019] <Mixed Solvent (D)> The mixed solvent (D) is a mixture of water (B) and an organic solvent (C). In the present invention, the Hansen solubility parameter of the mixed solvent (D) is 51.2 MPa as the sum of the polarity term and the hydrogen bond term. 0.5 More than 57.7MPa 0.5 Less than 51.7MPa, preferably 51.7MPa 0.5 More than 57.2MPa 0.5 It is adjusted within the following ranges:
[0020] Here, the Hansen Solubility Parameter (hereinafter referred to as "HSP value") is an index that indicates the solubility of a substance, i.e., how easily a substance can be dissolved in another substance. The HSP value is also used not only to judge solubility, but also to evaluate the aggregation and decomposition of fine particles in a solvent, such as how easily a substance can exist in another substance, i.e., how good the dispersibility is, and can be used as a judgment index. In general, various interaction forces such as London dispersion forces, hydrogen bond forces, dipole-dipole forces, induction effects, coordinate bond forces, and obstacle repulsion forces are thought to be at work between molecules such as between solutes and solvents, between polymers and solvents, and between polymers and polymers. Hansen considered that the three main interaction forces that make up the cohesive energy of a substance are (1) London dispersion forces, (2) dipole-dipole forces, and (3) hydrogen bonding forces, and proposed a solubility parameter by dividing the cohesive energy term of the Hildebrand solubility parameter (δ) into three interaction terms. Here, the dispersion term δD indicates the effect due to dispersion forces, the polar term δP indicates the effect due to dipole-dipole forces, and the hydrogen bond term δH indicates the effect due to hydrogen bonding forces. dD (dispersion term) = δD: Energy derived from intermolecular dispersion forces dP (polar term) = δP: Energy derived from intermolecular polar forces dH (hydrogen bond term) = δH: Energy derived from hydrogen bonding forces between molecules (where the units are MPa) 0.5 ). That is, the dispersion term reflects van der Waals forces, the polar term reflects dipole moments, and the hydrogen bond term reflects the effects of water, alcohol, etc.
[0021] In the present invention, the reason for focusing on the polarity term and hydrogen bond term of the HSP value and defining it as "polarity term + hydrogen bond term" is as follows. That is, colloid chemistry can be used to disperse hydrophobic fine powder particles in a mixed solvent mainly composed of water. However, to disperse hydrophobic fine powder particles in a mixed solvent mainly composed of water, it is necessary to consider the type and number of hydrophilic polar groups, the molecular state, etc., and it is complicated to quantitatively explain it using colloid chemistry. Therefore, the concept of HSP value, which takes into account the type and number of polar groups and the molecular state, is used, which is said to be simple and can show appropriate results in many cases. Here, the concept of dividing the surface free energy into components is that the hydrogen bond component and the polar component are considered together as the polar component (or hydrogen bond component), in other words, the components can be divided into two components, the dispersion component and the polar component, which dominates the majority of theories. In order to disperse hydrophobic fine particle powder in a mixed solvent, the "dispersion term" of the HSP value is also necessary. However, if one focuses primarily on the dispersion term, although the hydrophobic fine particle powder disperses in the mixed solvent, the resulting coating film may not exhibit super-water repellency. Experiments have revealed that the main parameter that achieves both "dispersion of hydrophobic fine particle powder" and "super-water repellency of the resulting coating film" in an aqueous system is the "polarity term + hydrogen bonding term," and so it was decided to use the "polarity term + hydrogen bonding term."
[0022] In this embodiment, the HSP value of the mixed solvent (D) is an average weighted by the volume ratio. For example, the hydrogen bond term (ΔH) of the Hansen solubility parameter of the mixed solvent (D) can be calculated by the following formula. Hydrogen bond term (δH) = [{(δH of water (B)) × (volume of water in mixed solvent (D)%)} / 100] + [{(δH of solvent (C)) × (volume of solvent (C) in mixed solvent (D)%)} / 100] More specifically, for example, the HSP value of a mixed solvent (D) obtained by mixing water (B) (δD(B), δP(B), δH(B)) and solvent (C) (δD(C), δP(C), δH(C)) in a volume ratio of 1:1 can be calculated as (0.5·δD(B)+0.5·δD(C),0.5·δP(B)+0.5·δP(C),0.5·δH(B)+0.5·δH(C)). The HSP value of the mixed solvent (D) can be calculated as described above, and the "polarity term + hydrogen bond term" focused on in the present invention is the sum of the polarity term ΔP and the hydrogen bond term ΔH of the HSP value of the mixed solvent (D) calculated above.
[0023] Here, the data used in calculating the HSP value will be explained. There are known values for various resins and solvents, and these may be used as they are, but in the present invention, the calculation is performed using values calculated using computer software HSPiP (Hansen Solubility Parameters in Practice). This HSPiP also has a database of resins and solvents, and in the present invention, the following database is referenced. HSPiP(Hansen Solubility Parameters in Practice) ver4. 1.07 The specific values of the HSP data (δD, δP, δH) used this time are as follows: ·Wed:(15.5,16,42.3) Isopropyl alcohol: (15.8, 6.1, 16.4) Acetone: (15.5, 10.4, 7.0) Ethyl acetate: (15.8, 5.3, 7.2) 2-Methoxyethanol: (16,8.2,15) Ethylene glycol: (17, 11, 26)
[0024] <Water (B)> In the present invention, water (B) is mainly used to adjust the viscosity of the paint.
[0025] <Organic solvent (C)> The use of the organic solvent (C) makes it easier for the hydrophobic fine particle powder to disperse in water. The organic solvent (C) may be a water-soluble organic solvent or a water-insoluble organic solvent. Specific examples are as follows. Hydrocarbon solvents Toluene, xylene, solvent naphtha, isohexane, cyclohexane, methylcyclohexane, n-heptane, n-decane, heptane, ethylbenzene, etc. Alcohol-based solvents Methanol, ethanol, propanol, isopropanol, butanol, isobutanol, t-butanol, sec-butanol, pentanol, hexanol, benzyl alcohol, etc. Ketone-based solvents Acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclohexanone, diacetone alcohol, etc. Ester-based solvents Methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, etc. Ether solvents Diethyl ether, diisopropyl ether, methyl cellosolve, ethyl cellosolve, butyl cellosolve, dioxane, methyl tertiary butyl ether, etc. Glycol-based solvents Ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,6-hexanediol, 2,2-dimethyl-1,3-propanediol, etc. Glycol ester solvent Ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, etc. Glycol ether solvents Diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, triethylene glycol monomethyl ether, propylene glycol monomethyl ether, propylene glycol monobutyl ether, 3-methoxy-3-methyl-1-butanol, etc. Glyme-based solvents Ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, diethylene glycol dibutyl ether, dimethoxytetraethylene glycol, dipropylene glycol dimethyl ether, etc. Halogen-based solvents Dichloromethane, chlorobenzene, methyl bromide, trichloroethylene, 1-bromopropane, etc. Nitrogen-containing solvents Acetonitrile, benzonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, N,N-dimethylacrylamide, N,N-dimethylacetoacetamide, N,N-diethylformamide, N,N-diethylacetamide, etc. Sulfur-containing solvents Dimethyl sulfoxide, sulfolane, thiodiethanol, etc.
[0026] Among these organic solvents, preferred are organic solvents that are at least partially soluble in water, and more preferred are organic solvents that are miscible with water. These may be used alone or in combination of two or more.
[0027] <Resin (E)> The coating composition containing the resin (E) is more likely to form a coating film. In the present invention, the content of the resin (E) is preferably more than 0 mass% and not more than 58 mass%, more preferably in the range of 2 mass% or more and not more than 58 mass%, based on 100 mass% of the total amount of the hydrophobic fine particle powder (A) and the resin (E). In the present invention, the resin (E) may be an aqueous emulsion resin, etc. Examples of the aqueous emulsion resin include vinyl acetate resins, ethylene vinyl acetate resins, phenol resins, epoxy resins, fluororesins, polyester resins, silicone resins, urethane resins, acrylic urethane resins, acrylic silicone resins, acrylic resins, acrylic-styrene resins, and organic-inorganic polymer hybrid resins.
[0028] <Water-soluble polymer> Water-soluble polymers are used for purposes such as thickening, gelling, emulsifying, protective colloidal, dispersing, film-forming, binding, foam stabilizing, preventing redeposition, reducing surface tension, moisturizing, sequestering metal ions, antistatic, adhesive, and water absorption, and are specifically applied to products in a wide range of industrial fields, such as detergents, cosmetics, food, pharmaceuticals, paints, and civil engineering. The characteristic of water-soluble polymers is that they have a molecular weight of approximately 10,000 or more, are molecules that have the property of dissolving in water, and when dissolved in water, they form a hydrogel that contains a lot of water around the molecules. By using water-soluble polymers in paints, the water-soluble polymers remain in the film even after the coating film dries, and because they are compatible with water, they have the characteristic of reducing the durability of the coating film, so in the present invention, water-soluble polymers are a component that should not be used in practice. Specifically, water-soluble polymers are classified into natural polymers, semi-synthetic polymers, and synthetic polymers. Examples of water-soluble natural polymers include guar gum, carrageenan, sodium alginate, corn starch, xanthan gum, sodium chondroitin sulfate, sodium hyaluronate, etc.; examples of water-soluble semi-synthetic polymers include carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, cationized guar gum, etc.; and examples of water-soluble synthetic polymers include carboxyvinyl polymer, polyacrylic acid, polyvinylpyrrolidone, polyvinyl alcohol, etc.
[0029] The superwater-repellent coating composition according to the present invention may contain other components in addition to the water-soluble polymer, as required, such as coloring pigments, extender pigments, thickeners, curing agents or curing catalysts, defoamers, antioxidants, UV absorbers, light stabilizers, surface conditioners such as leveling agents and flow-stopping agents, pigment dispersants, film-forming assistants, antifreeze agents, wetting agents, penetration assistants, preservatives, matting agents, heat-shielding agents, pH adjusters, surfactants, plasticizers, antiskinning agents, fiber materials, etc. As mentioned above, the superwater-repellent coating composition according to the present invention is substantially free of water-soluble polymers. However, the term "substantially free" is used because the composition may contain water-soluble polymers at the impurity level.
[0030] Next, a method for preparing the superwater-repellent coating composition according to the present invention will be described. The method for preparing the super water repellent coating composition according to the present invention is not particularly limited to the order or steps of mixing the materials, but from the viewpoint of ease of stirring, the composition can be prepared by adding the hydrophobic fine particle powder (A) and the resin (E) to a mixed solvent (D) of water (B) and an organic solvent (C), further adding additives as necessary, and stirring with a stirrer. As a stirring method, no special method is required, and a method commonly used by those skilled in the art can be used. For example, a high-speed stirrer such as a homomixer or homogenizer, a kneader, an ultrasonic disperser, a ball mill, or a hand mixer can be used.
[0031] The coating composition according to the present invention can be applied by known application methods such as spray coating with an air spray, airless spray or the like, brush coating, spatula coating, roller coating, applicator, bar coder or the like. The coating composition according to the present invention can be applied regardless of the roughness of the substrate.Specific examples of substrates to which the coating composition according to the present invention can be applied include unformed refractory materials, bricks, pottery, spray coatings, flexible hoses, steel plates, tinplates, galvanized steel plates and galvanized steel plates, metal plates such as aluminum, glass plates, hard boards, gypsum boards, fiber-reinforced cement boards, flexible boards, cement mortar boards, perlite boards, wood, asphalt blocks, stone materials, plastic boards, synthetic resins, and other materials, or coatings formed on materials.In particular, the coating composition according to the present invention increases the adhesive strength when applied to unformed refractory materials, bricks, pottery, spray coatings, wood, stone materials, and other objects with uneven surfaces.The effect of the superwater-repellent film is that it is difficult for contaminants, such as aqueous solutions of iron powder and dust containing water, to adhere to the substrate. Furthermore, even if contaminants adhere to the surface of the super water-repellent coating, the contaminants are captured as rainwater or other water droplets roll off the surface, and the dirt washes off along with the droplets, improving the cleaning effect compared to conventional coatings. The coating also exhibits the same effect against chemicals that corrode equipment, such as aqueous solutions of ammonia water, sulfuric acid, and hydrochloric acid, and is expected to have an inhibitory effect on equipment corrosion. Furthermore, the coating exhibits release properties for clay minerals, cement, and refractories that contain water. EXAMPLES
[0032] Next, the present invention will be described in more detail based on examples, but the present invention is not limited thereto. The detailed compounding ratios of the examples will be described later in Table 1 together with the evaluation results.
[0033] <Comparative Example 1> Hydrophobic fine particle powder (A) is amorphous silica Leoloseal (registered trademark) HM-30S (BET specific surface area m 2 A coating composition was prepared by stirring at 10,000 rpm for 30 minutes using only water as a solvent and a high-speed stirrer (A: 205±20 / g, carbon mass%: 3.5, M value vol%: 64, manufactured by Tokuyama Corporation). This coating composition was prepared so that the content of (A) in 100% by weight of the coating composition was 4.7% by weight. <Comparative Example 2> Isopropyl alcohol was added as the organic solvent (C) to the formulation of Comparative Example 1, and the mass ratio of (B) to (C) was adjusted to 90:10. <Example 1> A coating composition was prepared in the same manner as in Comparative Example 2, except that an acrylic silicone emulsion was added as the resin (E) so that the mass ratio of the hydrophobic fine particle powder (A) to the resin (E) was adjusted to 98:2.
[0034] The following is an example in which the mass ratio of (A) and (E) was varied in the same manner as in the production method of Example 1. <Example 2> Based on the ratios in Example 1, a coating composition was prepared with a mass ratio of (A) to (E) of 80:20. <Example 3> Based on the ratios in Example 1, a coating composition was prepared with a mass ratio of (A) and (E) of 60:40. <Example 4> Based on the ratios in Example 1, a coating composition was prepared with a mass ratio of (A) and (E) of 42:58. <Comparative Example 3> Based on the ratio in Example 1, a coating composition was prepared with a mass ratio of (B) and (C) of 70:30. <Comparative Example 4> Based on the ratios in Comparative Example 3, a coating composition was prepared with a mass ratio of (A) and (E) of 80:20. <Comparative Example 5> Based on the ratios in Comparative Example 3, a coating composition was prepared with a mass ratio of (A) and (E) of 60:40. <Comparative Example 6> Based on the ratios in Comparative Example 3, a coating composition was prepared with a mass ratio of (A) and (E) of 42:58.
[0035] The following is an example in which the sum of the polarity term and the hydrogen bond term in the HSP value of the mixed solvent (D) in the coating composition was varied in the same manner as in the manufacturing method of Example 1. <Comparative Example 7> The proportions of (A) and (E) in 100% by mass of the coating composition are fixed at 4.7% by mass and 3.3% by mass, respectively, and the sum of the polarity term and hydrogen bond term is 58.3 MPa. 0.5 Thus, a coating composition was prepared. <Example 5> The sum of the polarity term and hydrogen bond term based on the ratio of Comparative Example 7 is 57.2MPa. 0.5 Thus, a coating composition was prepared. <Example 6> The sum of the polarity term and hydrogen bond term based on the ratio of Comparative Example 7 is 56.1MPa. 0.5 Thus, a coating composition was prepared. <Example 7> The sum of the polarity term and hydrogen bond term based on the ratio of Comparative Example 7 is 53.9 MPa. 0.5 Thus, a coating composition was prepared. <Example 8> The sum of the polarity term and hydrogen bond term based on the ratio of Comparative Example 7 is 51.7MPa. 0.5 Thus, a coating composition was prepared. <Comparative Example 8> The sum of the polarity term and hydrogen bond term based on the ratio of Comparative Example 7 is 49.6MPa. 0.5 Thus, a coating composition was prepared.
[0036] The following is an example in which the mass ratios of (A) and (E) in the coating composition were fixed at 59:41 and (B) and (C) at 85:15, respectively, in the same manner as in Example 1, and the content of (A) was varied. <Example 9> A coating composition was prepared by fixing the mass ratio of (A) to (E) at 59:41 and setting the content of (A) at 0.5 mass %. <Example 10> A coating composition was prepared using the ratios in Example 9 as a base, but with the content of (A) set to 4.0 mass %. <Example 11> A coating composition was prepared using the ratios in Example 9 as a base, but with the content of (A) set to 8.2 mass %. <Comparative Example 9> A coating composition was prepared using the ratios in Example 9 as a base, but with the content of (A) set to 10.9 mass %.
[0037] The following is an example in which the type of (A) was changed in the same manner as in Example 1. <Example 12> Based on the ratio of Example 7, AEROSIL (registered trademark) RY300 (BET specific surface area m 2 A coating composition was prepared using a cellulose acylate copolymer (manufactured by Nippon Aerosil Co., Ltd.) having a molecular weight of 1.00 to 1.500 kg / g, carbon mass %: 6.0 to 8.5, M value vol %: 69. <Example 13> Based on the ratio in Example 7, AEROXIDE (registered trademark) Alu C 805 (BET specific surface area m 2 A coating composition was prepared using a cellulose acylate copolymer (manufactured by Nippon Aerosil Co., Ltd.) having a molecular weight of 1.0001 to 1.0001, a carbon content of 3.5 to 4.5, and an M value of 70 (vol %). <Example 14> Based on the ratio of Example 7, AEROXIDE (registered trademark) TiO2NKT90 (BET specific surface area m 2 A coating composition was prepared using a cellulose acylate copolymer (manufactured by Nippon Aerosil Co., Ltd.) having a molecular weight of 1.00 to 1.000 mm / g and a carbon content of 2.5 to 4.5 mass % and M value vol % of 25. <Example 15> Based on the ratio of Example 7, (A) was used, and Leoloseal (registered trademark) DM-30S (BET specific surface area m 2 / g: 230±20, carbon mass%: 2.2, M value vol%: 52, manufactured by Tokuyama Corporation) was used to prepare a coating composition. <Example 16> Based on the ratio of Example 7, (A) was used, and Leoloseal (registered trademark) KS-20SC (BET specific surface area m 2 / g: 160±20, carbon mass%: 2.0, M value vol%: 55, manufactured by Tokuyama Corporation) was used to prepare a super water-repellent coating composition. <Comparative Example 10> Based on the ratio of Example 7, (A) was used, and Leoloseal (registered trademark) DM-10 (BET specific surface area m 2 / g: 120±20, carbon mass%: 0.9, M value vol%: 48, manufactured by Tokuyama Corporation) was used to prepare a coating composition. <Comparative Example 11> Based on the ratio of Example 7, (A) was used, and Leoloseal (registered trademark) MT-10 (BET specific surface area m 2 / g: 120±20, carbon mass%: 0.9, M value vol%: 47, manufactured by Tokuyama Corporation) was used to prepare a coating composition.
[0038] The following is an example in which the type of (C) was changed in the same manner as in Example 1. <Example 17> A coating composition was prepared based on the ratios in Example 7, using acetone as (C). <Example 18> A coating composition was prepared based on the ratios in Example 7, using ethyl acetate as (C). <Example 19> A coating composition was prepared based on the ratio of Example 7, using 2-methoxyethanol as (C). <Example 20> A coating composition was prepared based on the ratio of Example 7, using ethylene glycol as (C).
[0039] The following is an example in which the type of (E) was changed in the same manner as in Example 1. <Example 21> A coating composition was prepared based on the ratio of Example 7, using an acrylic emulsion as (E). <Example 22> A coating composition was prepared based on the ratio of Example 7, using an acrylic urethane emulsion as (E). <Example 23> A coating composition was prepared based on the ratio of Example 7, using a urethane emulsion as (E). <Example 24> A coating composition was prepared based on the ratio of Example 7, using an epoxy emulsion as (E). <Example 25> A coating composition was prepared using the ratio of Example 7 as a base and a fluorine emulsion as (E).
[0040] <Comparative Example 12> Following Example 20 of Patent Document 1, a mixture of (A) Reolosil (registered trademark) HM-30S and (C) isopropyl alcohol was added to a solution of water and hydroxyethyl cellulose (HEC), a water-soluble polymer, and dispersed for 20 minutes at 10,000 rpm with a high-speed stirrer, and then mixed with (E) acrylic silicone emulsion and stirred for 10 minutes at 1500 rpm with a high-speed stirrer to prepare a coating composition. This coating composition was prepared so that the mass ratio of (A) to HEC was 9:1 and the content of (A) was 2 mass%.
[0041] The following is an example in which the amount of (A) added was varied in the same manner as in Comparative Example 12. <Comparative Example 13> The mass ratios of (A) to HEC and (A) to (E) were the same as in Comparative Example 12, but the amounts of (A), HEC, and (E) added were doubled. The mass ratio of water to isopropyl alcohol was the same as in Comparative Example 12, but the amounts of (B) and (C) added were reduced to prepare a coating composition.
[0042] The following is an example in which the amounts of the components that increase the adhesive strength of (E) and HEC were varied in the same manner as in the production method of Comparative Example 12. <Comparative Example 14> Following the procedure of Example 7, a coating composition was prepared in which (A), (B), and (C) were the same as in Example 7, the mass ratio of (A) to HEC was the same as in Comparative Example 12, and the combined amount of HEC and (E) was the same as in the composition of (E) in Example 7.
[0043] The coating compositions of the above examples were evaluated as follows from the viewpoints of dispersibility of the hydrophobic fine particle powder in water, and water repellency and durability of the coating film. <Dispersibility> To evaluate the dispersibility of the hydrophobic fine particle powder in water, a homomixer was used to disperse the powder at 10,000 rpm for 30 minutes. The resulting coating composition was visually inspected and the dispersion state was evaluated according to the following three-level evaluation criteria. Scores A and B were considered to be acceptable (good). Rating A: Disperses easily and does not settle or float after standing. Rating B: The powder disperses easily, but some of the powder settles or floats after standing for a certain period of time. Rating C: The powder cannot be dispersed at all, or all of the powder settles or floats after standing.
[0044] <Water repellency> To evaluate the water repellency of the coating film, the coating composition of each example was applied with a brush to a 50 x 50 x 0.5 mm (no undercoat) surface of a SUS430 substrate (surface treatment #400 finish) and dried at room temperature for 24 hours to obtain a coating film. Water repellency was confirmed by dripping ion-exchanged water onto the obtained coating film, and it was evaluated according to the following four-level evaluation criteria. Scores A and B were considered to be acceptable (good). Rating A: A board is placed on the horizontal part and the water droplets roll off naturally. Rating B: When the plate is tilted by 15°, the water droplets roll off. Rating C: When the plate is tilted by 15°, the water droplets roll off but leave water marks. Rating D: Water droplets do not roll even when the plate is tilted by 15°. In Table 1, "-" indicates that the dispersibility was rated C and therefore could not be evaluated.
[0045] <Durability> To evaluate the durability of the coating film, the coating composition of each example was applied with a brush onto the same substrate as that used in the evaluation of water repellency, and dried at room temperature for 24 hours to obtain a coating film. This was immersed horizontally in 150 mL of ion-exchanged water in a polypropylene container measuring 100 mm long x 100 mm wide x 40 mm high. Evaluation was performed every 10 days (up to 90 days) (〇: A plate was placed on the horizontal part, and water droplets rolled naturally, or the plate was tilted 15° and the water droplets rolled down, ×: The water droplets rolled when the plate was tilted 15°, but water marks were left or the plate did not roll down, or the coating film fell off and floated on the water surface, making it impossible to evaluate), and the number of days when the rating was × was evaluated according to the following evaluation criteria. Ratings A and B were considered to be pass. Grade A: 61 days or more Grade B: 31-60 days Grade C: 20-30 days Grade D: Less than 20 days In the table, "-" indicates that the evaluation of dispersibility was graded C or the evaluation of water repellency was graded D, and thus evaluation was not possible. In addition, in Comparative Example 2, the coating film did not function satisfactorily, so durability was not evaluated. Therefore, it is also indicated with "-".
[0046] [Table 1]
[0047] In Table 1, Examples 1 to 25 are coating compositions within the scope of the present invention, and were evaluated as good in all respects for dispersibility, water repellency, and durability. In contrast, Comparative Examples 1 to 14 are coating compositions outside the scope of the present invention, and were evaluated as poor in at least one of dispersibility, water repellency, and durability. The evaluation results will be specifically described below. First, from Comparative Example 1, it was confirmed that when the solvent was only water, the hydrophobic fine particle powder did not disperse. Moreover, it was confirmed from Comparative Example 2 that the coating film would not function satisfactorily if the resin (E) was not contained.
[0048] Next, from Examples 1 to 4, it was confirmed that the mass ratio of the hydrophobic fine particle powder (A) to the resin (E) is preferably in the range of 98:2 to 42:58. That is, it was confirmed that the content of the resin (E) in the total amount of the hydrophobic fine particle powder (A) and the resin (E) is preferably in the range of 2 mass% or more and 58 mass% or less. From this result, it was determined that the lower limit of the content of the resin (E) should be more than 0 mass%. Furthermore, it was confirmed from Comparative Examples 3 to 6 that even if the content of resin (E) was within the preferred range, if the sum of the polar term and the hydrogen bond term was outside the range of the present invention, the water repellency was not achieved. This is considered as follows. [Consideration 1] Hydrophobic microparticle powders exhibit water repellency due to the presence of many hydrophobic groups around the powder. However, when the organic solvent increases in the coating composition, the organic solvent interacts with the hydrophobic groups of the hydrophobic microparticles, causing the hydrophobic microparticle powder to become wet. Wetting makes it easier for water molecules to interact with each other, resulting in further wetting. As wetting progresses, the lotus effect becomes less likely to be expressed, which is thought to result in a decrease in water repellency. In addition, it is known that water molecules attached to hydrophobic microparticle powders are difficult to volatilize under room temperature conditions, and will remain in the film even after the film is formed. Therefore, it is thought that the water repellency of the film has decreased. [Consideration 2] When the amount of organic solvent in the paint composition increases, the hydrophilic aqueous emulsion resin aggregates and the specific surface area of the resin decreases. When this is made into a film and dried, the amount of hydrophobic fine powder adhering to the coating film decreases, which is thought to result in a decrease in water repellency.
[0049] Next, in Examples 5 to 8, better results were obtained compared to Comparative Examples 7 and 8. That is, the sum of the polar term and the hydrogen bond term was 51.7 MPa. 0.5 More than 57.2MPa 0.5 It was confirmed that the following range is preferable. From this result, the sum of the polar term and the hydrogen bond term is 51.2 MPa. 0.5 More than 57.7MPa 0.5 The following ranges were deemed acceptable:
[0050] Next, in Examples 9 to 11, better results were obtained compared to Comparative Example 9. From these results, it was determined that the content of the hydrophobic fine particle powder (A) should be more than 0 mass% and not more than 10 mass%, and that the content of the mixed solvent (D) is preferably 80 mass% or more.
[0051] Next, in Examples 12 to 16, better results were obtained compared to Comparative Examples 10 and 11. From these results, it was determined that super water repellency is exhibited by preparing a coating composition using a hydrophobic fine particle powder with a carbon content of 1.5 mass% or more, regardless of the type of hydrophobic fine particle powder or the type and number of hydrophobic functional groups. In addition, good dispersibility was obtained in Example 12, which used a hydrophobic fine particle powder with a carbon content of 6.0 to 8.5 mass%, so it was determined that dispersion is possible even for hydrophobic fine particle powder with a high carbon content.
[0052] Next, in Examples 17 to 20, good results were obtained even when the type of organic solvent (C) was changed. From these results, the sum of the polar term and the hydrogen bond term in the HSP value of the mixed solvent (D) was 51.2 MPa. 0.5 More than 57.7MPa 0.5 It was determined that various organic solvents, such as alcohols, ketones, esters, ethers, and glycols, could be used as long as they met the following criteria.
[0053] Next, good results were obtained even when the type of resin (E) was changed in Examples 21 to 25. From these results, it was determined that various resins such as acrylic silicone, acrylic, acrylic urethane, urethane, epoxy, and fluorine-based resins can be used, at least as long as they are water-based emulsion resins.
[0054] Comparative Examples 12, 13, and 14 were coating compositions containing a water-soluble polymer, and it was confirmed that the inclusion of a water-soluble polymer reduced the durability of the coating film.
Claims
1. A super water-repellent coating composition for forming a super water-repellent coating film on a substrate, comprising: A method for producing a water-soluble polymer dispersion comprising the steps of: (A) at least one hydrophobic fine particle powder; (D) a mixed solvent of water (B) and an organic solvent (C); and (E) a resin, the method comprising the steps of: the hydrophobic fine particle powder (A) has a carbon content of 1.5% by mass or more and a content thereof in the superwater-repellent coating composition of more than 0% by mass and 10% by mass or less; The Hansen solubility parameter of the mixed solvent (D) is 51.2 MPa, which is the sum of the polarity term and the hydrogen bond term. 0.5 More than 57.7MPa 0.5 The super water-repellent coating composition is as follows:
2. 2. The ultrawater-repellent coating composition according to claim 1, wherein the content of the mixed solvent (D) is 80 mass % or more.
3. 3. The ultrawater-repellent coating composition according to claim 1, wherein the resin (E) is at least one type of aqueous emulsion resin.
Citation Information
Patent Citations
Water-repellent coating material, its production and heat exchanger
JP1995166123A
Coating composition for hydrophobic film and article having hydrophobic surface
JP2022531471A
Super water-repellent coating composition
JP7129255B2
Dispersion and method for modifying a surface with hydrophobized silica
US20120114865A1
Water repellent agent and use thereof
WO2005063903A1